2017
DOI: 10.3389/fimmu.2017.01299
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Aggravates Hepatic Ischemia and Reperfusion Injury by Inhibiting Liver-Resident Macrophage M2 Polarization via C/EBP Homologous Protein-Mediated Endoplasmic Reticulum Stress

Abstract: Aggravated liver ischemia and reperfusion (IR) injury has been observed in hyperglycemic hosts, but its underlying mechanism remains undefined. Liver-resident macrophages (Kupffer cells, KCs) and endoplasmic reticulum (ER) stress play crucial roles in the pathogenesis of liver IR injury. In this study, we evaluated the role of ER stress in regulating KC activation and liver IR injury in a streptozotocin-induced hyperglycemic/diabetic mouse model. Compared to the control group (CON group), hyperglycemic mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 54 publications
2
31
1
Order By: Relevance
“…(17) Similarly, both IRE1α and CHOP have been found to suppress M2-like polarization of liver-resident macrophages, leading to excessive inflammation and exacerbation of liver injury. (16,18) In the present study, VDR deficiency increased expression of proinflammatory activation markers and decreased induction of alternative macrophage activation markers in the liver. In vitro experiments demonstrate that VDR activation inhibits proinflammatory activation and facilitates alternative polarization in BMDMs treated with ER-stress CM.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…(17) Similarly, both IRE1α and CHOP have been found to suppress M2-like polarization of liver-resident macrophages, leading to excessive inflammation and exacerbation of liver injury. (16,18) In the present study, VDR deficiency increased expression of proinflammatory activation markers and decreased induction of alternative macrophage activation markers in the liver. In vitro experiments demonstrate that VDR activation inhibits proinflammatory activation and facilitates alternative polarization in BMDMs treated with ER-stress CM.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, macrophage‐specific deletion of IRE1α restores the M2 polarization and decreases levels of proinflammatory cytokines . Similarly, both IRE1α and CHOP have been found to suppress M2‐like polarization of liver‐resident macrophages, leading to excessive inflammation and exacerbation of liver injury . In the present study, VDR deficiency increased expression of proinflammatory activation markers and decreased induction of alternative macrophage activation markers in the liver.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…What's more, HMGB1 neutralization treatment further protects against intestinal ischemia-associated liver damage in antibiotic induced microbiota-depleted rats CHOP over-activation inhibited M2 KCs polarization, leading to excessive intrahepatic inflammation and exacerbation of liver I/R injury. 59 Another research also found that spermine-mediated autophagy inhibits M1 polarization but promoting M2 polarization of KCs leading to attenuated thioacetamide-induced liver injury. 60 Previous researches already demonstrated that systemic depletion of macrophages prevents hippocampal neuroinflammation and memory dysfunction after experimental tibial fracture, 61 improves renal I/R injury, 62 and decreases inflammatory mediators in endotoxin-treated rats.…”
Section: Discussionmentioning
confidence: 98%
“…The role of KC M1/M2 polarization in different liver diseases and injuries has been reported in many studies. A recent study showed that in a mouse liver ischemia/reperfusion model, hyperglycemia-induced CHOP over-activation inhibited KC M2 polarization, leading to excessive intrahepatic inflammation and exacerbation of liver IR injury ( 43 ). Nogo-B was shown to be permissive for M1 polarization in KCs by inhibiting ER stress, thereby accentuating liver injury in alcoholic liver disease in humans and mice ( 44 ).…”
Section: Discussionmentioning
confidence: 99%